2020
DOI: 10.3390/d12120477
|View full text |Cite
|
Sign up to set email alerts
|

Resource Partitioning of Sympatric African Wolves (Canis lupaster) and Side-Striped Jackals (Canis adustus) in an Arid Environment from West Africa

Abstract: Knowledge on interference competition between species, particularly for scarce crucial resources, such as water, is a topic of increasing relevance for wildlife management given climate change scenarios. This study focuses on two sympatric canids, the African wolf and the side-striped jackal, to evaluate their group size and spatiotemporal activity patterns in the use of a limited resource by monitoring artificial waterholes in a semi-arid environment located in Senegal (West Africa). Remote cameras were deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Indeed, Karanth et al 34 found a large overlap in diel activity patterns between tigers (Panthera tigris) and leopards (Panthera pardus), while demonstrating their behavioral avoidance by using the time-to-encounter analysis. Similarly, Paúl et al 39 also found a large overlap in diel activity patterns between side-striped jackals (Canis adustus) and African wolves (Canis lupaster), while indicating the occurrence of some behavioral avoidance using the time-to-encounter analysis, with side-striped jackals taking longer than expected to be detected after the occurrence of African wolves. These results suggest that the evaluation of behavioral avoidance at ne time scales using the time-to-encounter analysis may provide an understanding of the mechanisms of species coexistence that cannot be detected by only estimating the temporal overlap.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Indeed, Karanth et al 34 found a large overlap in diel activity patterns between tigers (Panthera tigris) and leopards (Panthera pardus), while demonstrating their behavioral avoidance by using the time-to-encounter analysis. Similarly, Paúl et al 39 also found a large overlap in diel activity patterns between side-striped jackals (Canis adustus) and African wolves (Canis lupaster), while indicating the occurrence of some behavioral avoidance using the time-to-encounter analysis, with side-striped jackals taking longer than expected to be detected after the occurrence of African wolves. These results suggest that the evaluation of behavioral avoidance at ne time scales using the time-to-encounter analysis may provide an understanding of the mechanisms of species coexistence that cannot be detected by only estimating the temporal overlap.…”
Section: Introductionmentioning
confidence: 82%
“…4 and 5). However, many previous studies disregarded the effects of this order 34,37,38,68 (but also see Paúl et al 39 ). This study suggested the necessity of the time-to-encounter analysis with the species-occurrence order replacement, if the competitive dominances among focal species are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations